2014
DOI: 10.1371/journal.pone.0097007
|View full text |Cite
|
Sign up to set email alerts
|

Brain Remodelling following Endothelin-1 Induced Stroke in Conscious Rats

Abstract: The extent of stroke damage in patients affects the range of subsequent pathophysiological responses that influence recovery. Here we investigate the effect of lesion size on development of new blood vessels as well as inflammation and scar formation and cellular responses within the subventricular zone (SVZ) following transient focal ischemia in rats (n = 34). Endothelin-1-induced stroke resulted in neurological deficits detected between 1 and 7 days (P<0.001), but significant recovery was observed beyond thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…This suggested there were no side-effects from the surgery influencing the behavioral deficits on D8 and D15. These findings were consistent with previous findings in rodents7891011 and marmosets1213. In these researches, executive function, motor function and sensorimotor behavior was impaired after intracranial ET-1 injection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggested there were no side-effects from the surgery influencing the behavioral deficits on D8 and D15. These findings were consistent with previous findings in rodents7891011 and marmosets1213. In these researches, executive function, motor function and sensorimotor behavior was impaired after intracranial ET-1 injection.…”
Section: Discussionsupporting
confidence: 93%
“…ET-1 has recently been used to induce focal ischemia leading to impaired executive memory function and to impaired pure-motor and sensorimotor behaviors that are dependent on the specific area of ischemic insult in rodents7891011. There have been a few non-human primate studies utilizing ET-1 induced cerebral ischemia models developed in marmoset monkeys1213.…”
mentioning
confidence: 99%
“…ET-1 has been previously used to induce ischemic lesions in rat models of stroke. 37,47 Accordingly, we found that intra-BLA infusion of ET-1 (1-21) (3 mL/side, 400 pmol) induced a robust lesion in BLA ( Figure S5). Behaviorally, rats infused with ET-1 showed a significant reduction in the acquisition of a conditioned freezing response to the tone, in comparison to a saline-infused control group ( Figure 8B, day 21).…”
Section: Functional Rescue Of Cognitive Deficitsmentioning
confidence: 78%
“…This interval was based on pilot studies showing a significant impairment in fear acquisition combined with significant 385 neuronal injury approximately 21 days after the ET-1 stroke. The 21-day time point also 386 helped to maximize glial scar formation following ET-1 lesion (Abeysinghe et al, 2014), 387 an important factor to consider when using cell conversion strategies. ET-1 has been 388 previously used to induce ischemic lesions in rat models of stroke 23, 33 .…”
Section: Functional Rescue Of Memory Deficits 375mentioning
confidence: 99%